Maternal Disorders Associated with Morbidity and Mortality in a Metropolis of Kazakhstan - Aigerim Turekulova; Nurzhamal Dzhardemaliyeva; Alibek Mereke; Mukhtar Kulimbet (Clinics and Practice, 2025)
Background/Objectives: Hypertensive disorders of pregnancy, including pre-eclampsia and eclampsia, are leading causes of maternal morbidity and mortality worldwide and in Kazakhstan. This study aims to assess the burden of hypertensive disorders of pregnancy and main maternal disorders in Almaty, Kazakhstan, using the disability adjusted life years (DALY) methodology. Methods: We conducted a retrospective analysis of women aged 18 and above in Almaty, Kazakhstan, from 2018 to 2020. The medical claim data were retrieved from the Almaty city branch of the Republican Center for Electronic Health Care. Incidence-based DALY were calculated. Results: The total DALY increased for severe pre-eclampsia from 109.3 in 2018 to 187.2 in 2020 per 100,000 population and eclampsia from 3.1 in 2018 to 159.3 in 2020 per 100,000 population. Also, the 25–29 years age group had the largest increase in percent change (5.8) in the total DALY for hypertensive disorders of pregnancy. In addition, the 20–24 years age groups had the largest increase in percent change in the total DALY for severe pre-eclampsia (25.8) and eclampsia (80.5). Conclusions: Our findings highlight an increase in the burden of maternal disorders, especially for severe pre-eclampsia and eclampsia, in Almaty, Kazakhstan, from 2018 to 2020. Younger women bear a significant share of this burden, compounded by the pandemic’s impact on healthcare services.